Steady-state kinetics of reduction of coenzyme Q analogs by glycerol-3-phosphate dehydrogenase in brown adipose tissue mitochondria - Rauchová, H; Fato, R; Drahota, Z; Lenaz, G (Archives of biochemistry and biophysics, 1997)
We have undertaken a study of the role of coenzyme Q (CoQ) in glycerol-3-phosphate oxidation in mitochondrial membranes from hamster brown adipose tissue, using either quinone homologs, as CoQ1 and CoQ2, or the analogs duroquinone and decylubiquinone as artificial electron acceptors. We have found that the most suitable electron acceptor for glycerol-3-phosphate:CoQ reductase activity in situ in the mitochondrial membrane is the homolog CoQ1 yielding the highest rate of enzyme activity (225 +/- 41 nmol x min(-1) x mg(-1) protein). With all acceptors tested the quinone reduction rates were completely insensitive to Complex III inhibitors, indicating that all acceptors were easily accessible to the quinone-binding site of the dehydrogenase preferentially with respect to the endogenous CoQ pool, in such a way that Complex III was kept in the oxidized state. We have also experimentally investigated the saturation kinetics of endogenous CoQ (1.35 nmol/mg protein of a mixture of 70% CoQ9 and 30% CoQ10) by stepwise pentane extraction of brown adipose tissue mitochondria and found a K(m) of the integrated activity of glycerol-3-phosphate cytochrome c reductase for endogenous CoQ of 0.22 nmol/mg protein, indicating that glycerol-3-phosphate-supported respiration is over 80% of V(max) with respect to the CoQ pool. A similar K(m) of 0.19 nmol CoQ/mg protein was found in glycerol-3-phosphate cytochrome c reductase in cockroach flight muscle mitochondria.
Keywords: Mitochondria; Glycerolphosphate Dehydrogenase; ubichinon; transport elektronů; benzochinony; NADH-dehydrogenasa; Electron Transport Complex III; oxidace-redukce; hnědá tuková tkáň; Electron Transport; cytochromy skupiny c; Cricetinae; kinetika; Animals; glycerolfosfátdehydrogenasa; respirační komplex III; NADH Dehydrogenase; zvířata; Ubiquinone; Benzoquinones; Oxidation-Reduction; Adipose Tissue, Brown; Kinetics; mitochondrie; křečci praví; Cytochrome c Group